(untitled) (Raparin Journal of Humanities (RJH), 2023)
The current study aims to investigate the ESP courses at Salahaddin University-Erbil to identify the current situation of ESP programs and highlight the main challenges encountered by ESP instructors. The study hypothesizes that when the methodology and the principles of ESP are implemented appropriately in the courses at Salahaddin University, the teaching/learning process is likely to be more efficient. Moreover, when the ESP instructors understand the nature of ESP teaching, the quality of ESP courses can be improved. To achieve the aim of the study, the researchers employed a 20-question semi-structured interview for data collection; the study instrument was divided into several parts including instructors’ knowledge and expertise, conceptualizing the concept and the objectives of ESP, the nature of implementing the stages of ESP course design, the nature of collaboration, and instructors’ perceptions about the main issues. The sample of the study consisted of (7) instructors of ESP courses in non-English majors departments at Salahaddin University- Erbil. The collected data were analyzed qualitatively focusing on specific certain themes. Moreover, the results indicated that the ESP courses taught at Salahaddin University-Erbil did not meet the requirements of ESP courses. Besides, the instructors highlighted some main problems that led to the failure to achieve the objectives of the course; the reasons are the students’ poor linguistic level, time constraints, lack of background knowledge and linguistic literacy, large classes, and students’ low motivation.